2020
DOI: 10.3389/fbioe.2020.571192
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Generalized Ligament Laxity on the Deterioration of Hallux Valgus Deformity (Bunion)

Abstract: Hallux valgus is a common foot problem affecting nearly one in every four adults. Generalized ligament laxity was proposed as the intrinsic cause or risk factor toward the development of the deformity which was difficult to be investigated by cohort clinical trials. Herein, we aimed to evaluate the isolated influence of generalized ligament laxity on the deterioration using computer simulation (finite element analysis). We reconstructed a computational foot model from a mild hallux valgus participant and condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…It may require other compensatory strategy involving the hip adopted, resulting in a greater displacement of the centre of pressure in both anteroposterior and mediolateral direction [42]. The potential cause of this abnormal loading pattern is the poor alignment of the transverse tarsal joint and the ligament laxity [18]. A stable joint is linear so that force could transfer along the joint axis and the compression could distributed evenly to the joint surface [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may require other compensatory strategy involving the hip adopted, resulting in a greater displacement of the centre of pressure in both anteroposterior and mediolateral direction [42]. The potential cause of this abnormal loading pattern is the poor alignment of the transverse tarsal joint and the ligament laxity [18]. A stable joint is linear so that force could transfer along the joint axis and the compression could distributed evenly to the joint surface [40].…”
Section: Discussionmentioning
confidence: 99%
“…Some cadaveric researches found the alterations of mechanical loading such as joint reactive force [16], joints contact pressure [17] to show the implication of foot ligaments by ligament resection. Wong and his fellows [18] found that ligament laxity can result in forefoot abduction and inferred that it may be potentially coupled with pronation and arch collapse. Therefore, fully understanding of the abnormal loading conditions in the foot of the DS children during standing is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 21 ] predicted the metatarsal stress and pressure of a severe HV patient under a balanced standing condition using a comprehensive FE model of the foot and ankle complex. Wong et al [ 22 ] established a musculoskeletal model to explore the effect of ligament relaxation on the etiology of HV. The above studies are all based on the FE method to explore all kinds of foot problems.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies had investigated the biomechanics of hallux valgus deformity using finite element analysis. Wong et al (Wong et al, 2020) developed computational foot model from a mild hallux valgus participant and conducted a gait analysis to derive the simulation of walking. The effect of generalized ligament laxity on the stress pattern of the first ray had been studied.…”
Section: Introductionmentioning
confidence: 99%